ANALISIS SEMIOTIKA ROLAND BARTHES DALAM NOVEL PASUNG JIWA KARYA OKKY MADASARI - Zahra, Safira Amelia; Supena, Ahmad (Universitas Islam Sumatera Utara, 2024)
This research aims to describe the meaning of denotation, connotation and myth contained in several quotations from the novel